Association between depression and smoking: A global perspective from 48 low- and middle-income countries. (August 2018) - Stubbs, Brendon; Vancampfort, Davy; Firth, Joseph; Solmi, Marco; Siddiqi, Najma; Smith, Lee; Carvalho, Andre F.; Koyanagi, Ai
Abstract: Background: Smoking is a leading modifiable cause of global morbidity and mortality. Research from high-income countries has found a high prevalence of smoking among people with depression and suggested that this may partially contribute to the increased premature mortality in this population. Limited research has investigated smoking behaviors across the depression spectrum and in low- and middle-income countries (LMICs). This study explored the relationship between depression and smoking across 48 LMICs. Methods: We conducted a cross-sectional, community-based study comprising 242, 952 people [mean age 38.4 (SD = 16.1) years, 50.8% females] from the World Health Survey. Multivariable binary logistic regression analyses were performed to investigate the relationship between depression (including subsyndromal, brief depressive episode and depressive episodes) and smoking behaviours. Results: Overall, the prevalence of current smoking was lowest in Africa (13.5%) and highest in Asia (32.2%). A depressive episode was present in 6.7% of the sample. Compared to people without depression, subsyndromal depression, brief depressive episode, and depressive episodes were all significantly associated with smoking with similar effect sizes (ORs: 1.36–1.49). Countrywide meta-analysis found that the pooled overall OR for smoking in depression was 1.42 (95%CI = 1.32–1.52, I 2  = 39.7%). Furthermore, alcohol consumption and male gender were consistently associated with smoking across all regions and smoking was consistently less common in those who were wealthier and had a higher education. Conclusion: These data suggest that the depression spectrum is consistently associated with high levels of smoking behaivours in LMICs. Given that most of the world's smokers reside in LMICs, future smoking cessation interventions are required to target people with depression.